Forgetful Consumers and Consumption Tracking - Bao, Ying; Landry, Peter; Shi, Mengze (Management Science, 2025)
We study the market consequences of advances in consumption tracking technologies—such as mobile banking apps that help consumers monitor their spending and avoid overdrawn accounts—using a two-period consumption model. In the model, consumers pay a penalty fee if they consume in both periods. In the second period, consumers may be forgetful of their first-period consumption, although the use of consumption tracking can remind them. According to our analysis, the availability of consumption tracking often helps consumers at the expense of the firm; such benefits may be direct, where consumers make use of the technology to avoid penalty fees, or indirect, where the mere availability of consumption tracking forces the firm to lower its penalty fee. If consumers are partially sophisticated regarding their forgetfulness, however, the availability of consumption tracking may instill a false sense of security in that consumers expect to use consumption tracking to avoid penalty fees but ultimately, decide not to bother, making them especially susceptible to penalty fees. In some cases, the availability of consumption tracking may actually compel a firm to impose a penalty fee that would not otherwise be viable, leading to higher profits and lower consumer surplus. As we show, this scenario is attained within an intermediate range of forgetfulness and at a level of (partial) sophistication for which consumers overestimate their demand for the technology. This paper was accepted by Dmitri Kuksov, marketing. Funding: M. Shi appreciates financial support from HKUST Yuk-Shee Chan Professorship Fund and China NSF [Grant 72272036]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2023.00522 .